Rectal Cancer Modern Approaches to Treatment (Springer International Publishing, 2018)
Rectal Cancer: Modern Approaches to Treatment provides a useful overview of the multidisciplinary treatment of rectal cancer with a deeper dive into clinical challenges faced by treating physicians. Written by the leading experts in the field, it provides a practical management guide with an emphasis on the state-of-the-art that will be of value to both novices and experts engaged in rectal cancer treatment.